Discussing lifestyle behaviors: perspectives and experiences of general practitioners. Issue 1 (1st January 2019) - Hamilton, Kyra; Henderson, Joanna; Burton, Emma; Hagger, Martin S.
ABSTRACT: Background: Initiatives aimed at increasing participation in preventive health behaviors has been identified as a priority for addressing the increasing incidence of non-communicable chronic disease. General practice is an existing network that can be leveraged to intervene and promote messages for health behavior change. We aimed to explore the extent to which 'lifestyle' behaviors are discussed by general practitioners (GPs) with their patients in their practices, and the context and content of these discussions. Methods: GPs ( N  = 26) practising in Australian clinics participated in semi-structured interviews. Data were analyzed using an inductive thematic analysis. Results: Results showed discussions of lifestyle behaviors were brief, but relatively frequent and often initiated by the GP. GPs generally provided basic advice and education that was often ad-hoc and in reaction to prompts from the patient. GPs recognized the importance of addressing lifestyle behaviors in practice, but also highlighted substantive barriers that limit the initiation of these discussions. These included patient readiness for change, patient acceptance and openness, patient accountability and responsibility, patient background factors, GPs' role and knowledge, GP financial implications, GP-patient relationship, and lack of time. Conclusions: Current findings provide important preliminary knowledge on the extent to which Australian GPs discuss lifestyle behavior change with patients during routine consultations, the context and content of these discussions, and barriers to initiating these discussions. Further research should seek to gain a better understanding of barriers and identify strategies to mitigate their impact. This might maximize the potential for GPs to promote adaptive lifestyle behavior change for improving patient health.